PARADIGM OF TECHNOLOGY IN THE CONTEXT OF TECHNICAL SUBJECTS STUDIES PUBLICITY - TVARUZKA, Vaclav (Trends in education, 2017)
The paper deals with comparison of publicity of technology study fields in the Czech Republic in comparison with promotion of technological topics via retail chains and projects in Germany. The target is to show contemporary conceptions of presentation of technology and promotion of crafts in wider social and cultural context. The main method we used for analysis of information was critical interpretation of statistical data of educational structure development in higher professional education in the Czech Republic. There were a population of 15 years old pupils as an indication sample. By a comparison of statistics with a contemporary state and development trends, there is evident that official statistical data do not get the level of applicants and graduates quality and their interpretation about "not stopping of increase in technological fields" is possible to doubt. If we compare this data with number of students that graduated and stayed to work in their study field we find out that there is still a lack of technical staff and technological fields do not saturate needs of the community. We suggest to eliminate decrease of interest in technological study by bigger publicity of technology contribution and work for the quality of life. Very valuable material is a comparison of publicity clips in the Czech Republic and Germany, alternatively in retail chains.
Keywords: Paradigm of technology; promotion of the study; vocational education